Respuesta :

f(x) = 3x^2 + 1
g(x) = 1 - x
(f - g)(x) = 3x^2 + 1 - (1 - x) = 3x^2 + 1 - 1 + x = 3x^2 + x
(f - g)(2) = 3(2)^2 + 2 = 3(4) + 2 = 12 + 2 = 14.

If f(x) = 3x² + 1 and g(x) = 1 – x, the value of (f – g)(2) is 14

Further explanation

Function is a relation which each member of the domain is mapped onto exactly one member of the codomain.

There are many types of functions in mathematics such as :

  • Linear Function → f(x) = ax + b
  • Quadratic Function → f(x) = ax² + bx + c
  • Trigonometric Function → f(x) = sin x or f(x) = cos x or f(x) = tan x
  • Logarithmic function → f(x) = ln x
  • Polynomial function → f(x) = axⁿ + bxⁿ⁻¹ + ...

Recall the formulas related to the function such as :

[tex]( f + g )( x ) = f ( x ) + g ( x )[/tex]

[tex]( f - g )( x ) = f ( x ) - g ( x )[/tex]

[tex]( f \cdot g )( x ) = f ( x ) \cdot g ( x )[/tex]

[tex]\left ( \frac{f}{g} \right )(x) = \frac {f(x)}{g(x)} ~, ~ where ~ g(x) \neq 0[/tex]

Let us now tackle the problem!

Given:

[tex]f(x) = 3x^2 + 1[/tex]

[tex]g(x) = 1 - x[/tex]

Unknown:

[tex](f - g)(2) = ?[/tex]

Solution:

[tex]( f - g )( x ) = f ( x ) - g ( x )[/tex]

[tex]( f - g )( x ) = (3x^2 + 1) - (1 - x)[/tex]

[tex]( f - g )( x ) = 3x^2 + x[/tex]

[tex]( f - g )( 2 ) = 3(2)^2 + 2[/tex]

[tex]( f - g )( 2 ) = 12 + 2[/tex]

[tex]\large { \boxed {( f - g )( 2 ) = 14 } }[/tex]

Learn more

  • Inverse of Function : https://brainly.com/question/9289171
  • Rate of Change : https://brainly.com/question/11919986
  • Graph of Function : https://brainly.com/question/7829758

Answer details

Grade: High School

Subject: Mathematics

Chapter: Function

Keywords: Function , Trigonometric , Linear , Quadratic

Ver imagen johanrusli